Asuhan Kebidanan Komprehensif pada Ny. S di RSIA Masyita Makassar - Shaqila Ainurcynthia; Halida Thamrin; Azrida M (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Comprehensive care and Continuity of Care is a comprehensive approach in midwifery services that includes pregnancy, childbirth, postpartum period, newborn care, and family planning counseling. The goal is to provide integrated and adequate health services to reduce maternal mortality and improve the health of mothers and babies. This study aims to implement comprehensive midwifery care for Mrs.